Vitamin K: Infection, Inflammation, and Auto-Immunity - Xie Y; Li S; Wu D; Wang Y; Chen J; Duan L; Li S; Li Y (Journal of Inflammation Research, 2024)
Yuanyuan Xie,1,* Shifang Li,1,* Dinan Wu,2 Yining Wang,2 Jiepeng Chen,3 Lili Duan,3 Shuzhuang Li,4 Yuyuan Li2 1The First Affiliated Hospital of Dalian Medical University, Dalian, People’s Republic of China; 2Advanced Institute for Medical Sciences, Dalian Medical University, Dalian, People’s Republic of China; 3Sungen Bioscience Co., Ltd, Guangdong, People’s Republic of China; 4College of Basic Medical Science, Dalian Medical University, Dalian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuyuan Li; Shuzhuang Li, Tel +86 411 86118983, Email liyuyuan831221@163.com; shuzhuangli@126.comAbstract: Vitamin K (VK) comprises a group of substances with chlorophyll quinone bioactivity and exists in nature in the form of VK1 and VK2. As its initial recognition originated from the ability to promote blood coagulation, it is known as the coagulation vitamin. However, based on extensive research, VK has shown potential for the prevention and treatment of various diseases. Studies demonstrating the beneficial effects of VK on immunity, antioxidant capacity, intestinal microbiota regulation, epithelial development, and bone protection have drawn growing interest in recent years. This review article focuses on the mechanism of action of VK and its potential preventive and therapeutic effects on infections (eg, asthma, COVID-19), inflammation (eg, in type 2 diabetes mellitus, Alzheimer’s disease, Parkinson’s disease, cancer, aging, atherosclerosis) and autoimmune disorders (eg, inflammatory bowel disease, type 1 diabetes mellitus, multiple sclerosis, rheumatoid arthritis). In addition, VK-dependent proteins (VKDPs) are another crucial mechanism by which VK exerts anti-inflammatory and immunomodulatory effects. This review explores the potential role of VK in preventing aging, combating neurological abnormalities, and treating diseases such as cancer and diabetes. Although current research appoints VK as a therapeutic tool for practical clinical applications in infections, inflammation, and autoimmune diseases, future research is necessary to elucidate the mechanism of action in more detail and overcome current limitations.Keywords: vitamin K, VK-dependent proteins, infection, inflammation, auto-immune disease